CONTINUOUS USE OF ONLINE STORAGE SYSTEM FOR DOCUMENT SHARING (Jurnal Teknologi (Sciences & Engineering), 2015)
This paper discusses the use of online storage for document sharing to support teaching and learning purposes.  To date, online storage has become one of important tools for document storage and management.  Online storage has reduced the dependency to the storage devices that are bound to size limit, cost and risk.  A part of the storage capability, online storage can be used to share documents by allowing others to access the individual or a group of documents.   In this study online storage namely Dropbox has been used to share digital media such as notes, presentation materials and handouts to students.  Thus, the use of printed materials can be reduced.  In addition the documents can be safely kept and access at any time and location that are connected to the internet.   This study adapted Unified Theory of Acceptance and Use of Technology (UTAUT) to assess students’ perception and continuous use of Dropbox towards document sharing.  The findings revealed that students have positive perception towards Dropbox.  Furthermore, students have indicated that they are keen on continue using the Dropbox to support their learning.